Construction of grand staircase, Masjid Jamek / Nor Azrien Maaras - Maaras, Nor Azrien (Universiti Teknologi Mara, Perak, 2015)
History has literally been dug up at the confluence of the two rivers that inspired the name of Malaysia’s capital Kuala Lumpur. A staircase adjoining Masjid Jamek, long forgotten in the face of modernization and development, has been unearthed after works for the River of Life project in the area commenced. At a glance, it seems a disconnected structure but further digging showed there was more to it than it seems. Malaysian Institute of Architects (PAM) heritage conservation committee member and architect Mariana Isa said the staircase was part of the original mosque design from more than a hundred years ago. However, based on previous studies, maintenance is always been neglected and not become the main activity in managing and protecting of this valuable and non-replaceable asset. Therefore, the main objective of this study is to identify construction of Grand Staircase, Masjid Jamek, issues and problems affecting the implementation of maintenance in dealing with heritage Grand Staircase, Masjid Jamek.